γδ T Cells in the Tumor Microenvironment—Interactions With Other Immune Cells - Chan, Kok Fei; Duarte, Jessica Da Gama; Ostrouska, Simone; Behren, Andreas (Frontiers in Immunology, 2022)
A growing number of studies have shown that γδ T cells play a pivotal role in mediating the clearance of tumors and pathogen-infected cells with their potent cytotoxic, cytolytic and unique immune modulating functions. Unlike the more abundant αβ T cells, γδ T cells (up to 10% of the total human T cell populations) can recognize a broad range of tumors and infected cells without the requirement of antigen presentation via major histocompatibility complex (MHC) molecules. Instead, our group has recently demonstrated parts of the mechanisms of T cell receptor (TCR) dependent activation of Vγ9Vδ2+ T cells by tumors following the presentation of phosphoantigens, intermediates of the mevalonate pathway. This process is mediated through the B7 immunoglobulin family-like butyrophilin 2A1 (BTN2A1) and BTN3A1 complexes. Such recognition results in activation, a robust immunosurveillance process and elicits rapid γδ T cell immune responses. These include targeted cell killing, and the ability to produce large quantities of cytokines and chemokines to exert immune modulating properties and to interact with other immune cells. This immune cell network includes αβ T cells, B cells, dendritic cells, macrophages, monocytes, natural killer cells and neutrophils, hence heavily influencing the outcome of immune responses. This key role in orchestrating immune cells and their natural tropism for tumor microenvironment makes γδ T cells an attractive target for cancer immunotherapy. Here, we review the current understanding of these important interactions and highlight the implications of the crosstalk between γδ T cells and other immune cells in the context of anti-tumor immunity.